2017
DOI: 10.21548/12-1-2227
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Partial Defoliation on Quality Characteristics of Vitis vinifera L. cv. Cabernet Sauvignon Grapes 1. Sugars, Acids and pH

Abstract: The effect was studied of partial defoliation (33% and 66%) on the sugar and acid accumulation and pH in grapes of Vitis vinifera L. cv. Cabernet Sauvignon. Although the total soluble sugar (TSS) in grapes of partially defoliated vines was significantly higher than that of non-defoliated vines in some cases, no significant differences were generally found. No significant differences in total titratable acidity (TT A) were found between treatments. The timing of defoliation had no effect on TSS in grapes, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
46
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 29 publications
4
46
1
1
Order By: Relevance
“…In fact, berries from machine-pruned vines were smaller and with a higher amount of anthocyanin and tannin than those from cane-and spur-pruned vines, but the wine had the lowest quality score. Other researchers found similar results (Hunter et al, 1991;Johnstone et al, 1995), indicating that there is no linear, simple relationship between grape composition and wine quality. showed that this non-linear relationship may be due, amongst other factors, to the complexity of anthocyanin molecules, affecting time of extraction from Syrah grape skins during winemaking.…”
Section: Introductionmentioning
confidence: 57%
“…In fact, berries from machine-pruned vines were smaller and with a higher amount of anthocyanin and tannin than those from cane-and spur-pruned vines, but the wine had the lowest quality score. Other researchers found similar results (Hunter et al, 1991;Johnstone et al, 1995), indicating that there is no linear, simple relationship between grape composition and wine quality. showed that this non-linear relationship may be due, amongst other factors, to the complexity of anthocyanin molecules, affecting time of extraction from Syrah grape skins during winemaking.…”
Section: Introductionmentioning
confidence: 57%
“…Source-sink ratios play an important role in the seasonal variation of water and solute transport and accumulation in the grape berry. In this regard, the reaction of the vine depends largely on the level and timing of manipulation (Koblet 1987;Kliewer et al, 1988;Hunter et al, 1991;Poni et al, 1994;Kliewer & Dokoozlian 2005). As in most fleshy fruits, water and carbon transport into and out of grape berries is essential for volumetric growth and the accumulation of primary and secondary compounds, which determine the final fruit composition and quality (Coombe & McCarthy, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Macro-, meso-and micro-environmental conditions, as well as viticultural and oenological practices, would all affect these compounds either directly or indirectly via chemical and/or physical changes (Carbonneau et al, 2007;Iland et al, 2011). Together with, inter alia, soluble solids and titratable acidity (Hunter et al, 1991;Cliff et al, 2002;De Souza et al, 2005), the phenolic compounds therefore largely define the final wine quality.…”
Section: Introductionmentioning
confidence: 99%